Dynamic properties of Kermack-McKendrick-like models - Hamidou A. Diallo; Khalil Ezzinbi; Nisrine Outada; Gauthier Sallet (PLoS ONE, 2026)
We rigorously analyze the dynamic properties of Kermack-McKendrick-like compartmental models for infectious diseases, extending the classical SIR framework to include exposed individuals, mild and severe infections, hospitalization, and intensive care unit (ICU) compartments. Using a 13-compartment model, we establish mathematical results on well-posedness, the basic reproduction number R 0 , a first integral leading to a unique final epidemic size, and the global stability of the disease-free equilibrium under permanent immunity. When temporary immunity is included, we prove the existence of an endemic equilibrium for R 0 > 1. An age-stratified multi-group version of the model is also studied, demonstrating similar convergence properties and highlighting the impact of age structure on epidemic dynamics. Our results provide a rigorous mathematical framework for understanding how immunity duration, clinical progression, and age structure shape epidemic outcomes.